2011
DOI: 10.1002/rcm.5180
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenazone transformation products on light‐activated TiO2 surface by high‐resolution mass spectrometry

Abstract: The paper examines the transformation of phenazone (2,3-dimethyl-1-phenyl-3-pyrazolin-5-one), a widely used analgesic and antipyretic drug, under simulated solar irradiation in pure water, using titanium dioxide, and in river water. High-resolution mass spectrometry was employed to monitor the evolution of photoinduced processes. Initially, laboratory experiments were performed to simulate drug-transformation pathways in aqueous solution, using TiO(2) as photocatalyst. Thirteen main phenazone transformation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Calza et al reported the conversion of carbamazepine and clarithromycin in purified water using heterogeneous photocatalysis with TiO 2 . 96 For carbamazepine, 28 TPs were identified via MS fragmentation using LC/LTQ-Orbitrap-MS, formed by mono-, di-, trihydroxylation, oxidation, and ring contractions, leading to derivatives of 9-N-aminocarbonylacridine-9-carboxaldehydes. Similar reactions (hydroxylations, oxidations) and the cleavage of the sugar moiety cladinose led to the formation of 29 TPs when the macrolide antibiotic clarithromycin was present.…”
Section: ■ Pharmaceuticals and Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Calza et al reported the conversion of carbamazepine and clarithromycin in purified water using heterogeneous photocatalysis with TiO 2 . 96 For carbamazepine, 28 TPs were identified via MS fragmentation using LC/LTQ-Orbitrap-MS, formed by mono-, di-, trihydroxylation, oxidation, and ring contractions, leading to derivatives of 9-N-aminocarbonylacridine-9-carboxaldehydes. Similar reactions (hydroxylations, oxidations) and the cleavage of the sugar moiety cladinose led to the formation of 29 TPs when the macrolide antibiotic clarithromycin was present.…”
Section: ■ Pharmaceuticals and Hormonesmentioning
confidence: 99%
“…Calza et al reported the conversion of carbamazepine and clarithromycin in purified water using heterogeneous photocatalysis with TiO 2 . For carbamazepine, 28 TPs were identified via MS fragmentation using LC/LTQ-Orbitrap-MS, formed by mono-, di-, trihydroxylation, oxidation, and ring contractions, leading to derivatives of 9- N -aminocarbonylacridine-9-carboxaldehydes.…”
Section: Pharmaceuticals and Hormonesmentioning
confidence: 99%
“…[23][24][25][26] Mass spectrometry (MS) is the most selective technique to identify unknown compounds and, using electrospray ionization (ESI)-MS, it is possible to obtain structurally significant fragment ions. [27][28][29][30] Degradation products were characterized by multiple stage mass spectrometry (MS n ), using a high-resolution ion trap (LTQ-Orbitrap), acquiring spectra at a resolving power of 30 000, in order to confirm the elemental composition, together with high-resolution MS n detection, which provides diagnostic identification and characterization of metabolites.…”
Section: Rationalementioning
confidence: 99%
“…Hydroxyl radicals ( • OH) are the key species responsible for the oxidative destruction of environmental pollutants in many Advanced Oxidation Processes (AOPs) such as TiO 2 photocatalysis, H 2 O 2 /UV photolysis, sonolysis, γ-radiolysis etc., [1][2][3][4][5][6][7] and many biological processes including DNA damage, mutation and ageing. [8][9][10][11][12][13][14][15][16] The • OH induced destruction of emerging organic pollutants has been widely experimented [1][2][3][4]7,17,18 since the presence of pharmaceutically active compounds in the aquatic environment became an emerging environmental issue. [19][20][21][22] Pulse radiolysis studies reveal that • OH reacts with a large number of organic molecules with a nearly diffusion controlled rate.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Pulse radiolysis studies reveal that • OH reacts with a large number of organic molecules with a nearly diffusion controlled rate. 5,6,12,15,23,24 Furthermore, the ability to achieve complete mineralization 2,6 makes techniques of these kinds acceptable and environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%